Antecedents of Purchase Decision of Vape Users in Samarinda - Diah, Ahyar M.; Surahman, Surahman; Azizah, Amiril; Setiawan, Indra; Kintani, Aninda; Inggrid, Queen (Interdisciplinary Social Studies, 2023)
Background: Vape, sometimes known as "electronic cigarettes," first made its way into Indonesia in 2012. As technology advances, vaping's popularity there is still rising. The vast number of people who traveled abroad for vacation is where it all began. They brought vaporizers with them when they went back to Indonesia. They introduced them to friends, family, and coworkers in their various communities, which led to many people switching from traditional cigarettes to vaping and raising the price of vape in Indonesia. Aim: The purpose of this study was to analyze and prove the effect of perceived enjoyment, social influence, subjective norms, personal gratification on the attitude of vape users in Samarinda City. Method: Researchers conducted quantitative research by providing questionnaires to residents of Samarinda who use vaping products. The questionnaire contains 26 indicators and 26 statements scores on a scale of 1 to 5, with one strongly disagreeing and five strongly agreeing. The sample size for the SEM (Structural Equation Modeling) analysis tool is 100-200 respondents to estimate interpretations with SEM performed on the IBM AMOS 23 software. Findings: Perceived enjoyment, social influence, subjective norms, and personal gratification significantly effect the attitudes of vape users in Samarinda City. In addition, attitude and intention significantly affects purchase decisions for vape users in Samarinda City.